High performance boronic acid-containing hydrogel for biocompatible continuous glucose monitoring. Issue 66 (24th August 2017) - Dou, Qian; Hu, Debo; Gao, Hongkai; Zhang, Yongmei; Yetisen, Ali K.; Butt, Haider; Wang, Jing; Nie, Guangjun; Dai, Qing
Abstract : Rapid and robust hydrogels are essential in realizing continuous glucose monitoring in diabetes monitoring. Abstract : Rapid and robust hydrogels are essential in realizing continuous glucose monitoring in diabetes monitoring. However, existing hydrogels are limited in satisfying all of the sensory requirements such as detection range, response time, recoverability and biocompatibility. Here, we have developed a surface-initiated polymerization method to chemically immobilize a nano-boronic acid-hydrogel membrane onto a quartz crystal, then used a quartz crystal microbalance (QCM) to achieve real-time monitoring of glucose. The experimental results show that this hydrogel possesses enhanced binding properties to glucose under physiological conditions (pH 7.0–7.5) and blood glucose concentration (BGC) (1.1–33.3 mM). Moreover, our hydrogel displayed a rapid response time (∼100 s) to glucose, high biocompatibility in vivo through an animal model. The hydrogel has a great potential as a sensitive glucose probe for implantable continuous glucose sensors.